Care, competency, or honesty? Framing emergency preparedness messages and risks for nuclear energy in Singapore. (July 2020) - Ho, Shirley S.; Kim, Nuri; Looi, Jiemin; Leong, Alisius D.
Abstract: It is imperative to provide emergency preparedness messages so that the public can react appropriately to potential nuclear crises. Considering the mass media's extensive audience outreach, this study investigates how emergency preparedness message frames and the type of communication channels can influence individuals' trust in government, risk perceptions, and acceptance of nuclear energy development in a neighboring country. A 4 (Emergency preparedness message frame: competence vs. care vs. honesty vs. control) × 2 (Communication channel: social media vs. traditional media) between-subjects factorial experiment was conducted online with 600 participants. Messages centered on care influenced participants' trust in government the most. Messages disseminated through traditional media impacted participants' trust in government more than social media. Participants' trust in government and risk perceptions mediated the relationship between message frames and the types of communication channel on their acceptance of nuclear energy development in a neighboring country. Theoretical implications, practical implications, and directions for future research are discussed.